2021
DOI: 10.1021/acs.jproteome.1c00348
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Landscape of a Drug-Tolerant Persister Subpopulation of Mycobacterium tuberculosis

Abstract: Persisters are a subpopulation of bacteria that resist killing by antibiotics, even though they are genetically similar to their drug-susceptible counterpart. Like in several other bacteria, persisters are also reported in the human pathogen Mycobacterium tuberculosis (Mtb). Stochastic formation of Mtb persisters with a high level of antimicrobial tolerance set the stage for subsequent multidrug-resistant mutations. Despite significant advancement in our understanding, much remains to be learnt about the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…104, Table 2 ) (see Fig. S4A at the URL mentioned above) ( 50 ) and then confirmed by Southern blotting with the help of labeled probe (see Fig. S4B at the URL mentioned above).…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…104, Table 2 ) (see Fig. S4A at the URL mentioned above) ( 50 ) and then confirmed by Southern blotting with the help of labeled probe (see Fig. S4B at the URL mentioned above).…”
Section: Methodsmentioning
confidence: 82%
“…Although mHtpG is maintained by M. tuberculosis throughout the course of genetic evolution, we have yet to understand how M. tuberculosis is able to endure the loss of this protein. Hence, to enlighten the pathogen’s response to the loss of mHtpG and to further understand its effect on bacterial physiology, quantitative proteomics by isobaric tags for relative and absolute quantitation (iTRAQ) was performed with the whole-cell lysates (WCLs) of the wild-type and Δ htpG strains of M. tuberculosis H37Rv, typically as described previously ( 50 , 51 ). We adopted an 8-plex iTRAQ-based quantitative proteomics approach to identify proteins that exhibit a consistent pattern of expression across 4 biological replicates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The transcriptomic/proteomic data analyzed was collected in the absence of drug stimulation so we could hone in on native physiological and biochemical mechanisms/states that underlie drug resistance. Our study, therefore, does not address drug-induced changes in expression that may lead to phenotypic resistance in intrinsically drug sensitive isolates 23,24,40 . Emerging evidence that drug-induced proteomic changes can lead to drug tolerance/resistance in drug sensitive isolates is an important consideration that requires further investigation, particularly given the growing momentum in the field for widespread application of molecular testing.…”
Section: Discussionmentioning
confidence: 99%
“…To map the proteomic landscape of M. tuberculosis persisters, Sharma et al. has recently used iTRAQ‐based quantitative proteomics to study the H37Rv strain under ciprofloxacin and isoniazid treatment [77]. They observed that the persisters subpopulation has differential expression of proteins related to intermediary metabolism and respiration, cell wall processes, lipid metabolism, information pathways, virulence, detoxification, and adaptation.…”
Section: Studying Persister Cells By Proteomics: Challenges and Imple...mentioning
confidence: 99%